Ozone hole over poles : Current status (MAUSAM, 2011)
The ozone in the stratosphere is of great importance for very survival of life on the mother planet the Earth. Ozone acts as an umbrella and protects us from the harmful ultraviolet radiations coming from the Sun. The catalytic destruction of ozone by ClOx & NOx in general and ozone hole phenomenon over Antarctica during spring time in particular has generated unprecedented interest in monitoring of ozone and other trace constituents in the atmosphere. The satellites have proved to be an important tool to monitor the global ozone column on regular basis. The ozone data using various satellite platforms has been analyzed for the ozone hole studies over north and south poles. Also Ozone measurements were carried out at Maitri, Antarctica. The satellite data indicates that some recovery of ozone hole as a result of international efforts in reduction of use of CFCs which are the main culprit for ozone hole. However, it will be too early to conclude about ozone hole recovery. In the present communication current status of ozone hole will be discussed in detail.